Attitudes on fertility issues in breast cancer patients: an Italian survey. (June 2015) - Biglia, Nicoletta; Torrisi, Rosalba; D'Alonzo, Marta; Codacci Pisanelli, Giovanni; Rota, Selene; Peccatori, Fedro Alessandro
Abstract Background: Fertility issues should be discussed with young women before the start of any anticancer treatment. The study is aimed to investigate the attitude on fertility among Italian oncologists and breast surgeons dealing with BCa, and to report the consensus achieved on specific statements. Methods: One hundred and sixty-two panelists anonymously expressed an opinion through a web-based platform on 19 statements based on the Delphi method. Results: Ninety-one percent of oncologists considered important to discuss with patients about fertility issues and 83% believed estrogens could stimulate the growth of hidden cancer cells in ER+ tumors. Difficulties in accessing fertility preservation procedures were mainly due to patients' reluctance, but also to lack of coordination with the assisted reproduction specialists. No full consensus was reached on the prognostic role of pregnancy after BCa. Fifty-four percent of oncologists declared that pregnancy does not affect oncologic prognosis. Treatment with GnRHa during chemotherapy was considered the only mean for preserving ovarian function. Conclusions: Fertility preservation in BCa patients is a well-accepted practice among Italian oncologists. A poor knowledge of this specific issue emerged from the survey, even if a certain degree of agreement was observed on most fertility-related issues.